Italian schools in Minas Gerais: organization, curriculum and social relations - Maysa Gomes Rodrigues (Universidade Estadual de Maringá, 2014)
Current research discusses the organization of Italian schools (private or linked to charities) by their circumstances and curricula. The immigration phenomenon in Minas Gerais brought a large population of Italian immigrants on whose experience several schools were founded in some towns of the state of Minas Gerais,Brazil. Current essay investigates the common and differentiating factors of Italian Schools in the state? Documentary sources were analyzed on the organization of the following schools: Italian School linked to the Italian Beneficent Association in Belo Horizonte, and the schools Regina Margherita and Umberto Primo in Juiz de For a. The Umberto Primo school was associated to the Italian Society Umberto Primo and the Italian school Dante Alighieri was associated to the Società Dante Alighieri in Ouro Fino andUmbertoPrimoSchool in Nova Lima, linked to the Società Italiana of this town between 1899 and 1911. Current analysis contributes towards the clarification of similarities and differentiations on the organization of Italian Schools, and, inevitably, to the understanding of the schooling of immigrants in Minas Gerais.